Enteric virus in reclaimed water from treatment plants with different multi-barrier strategies: Trade-off assessment in treatment extent and risks - Rachmadi, Andri Taruna; Azizkhan, Zubair M.; Hong, Pei-Ying (The Science of the total environment, 2021)
Reclaimed water is an alternative water resource to mitigate water scarcity. To promote safe reuse, this paper aims to monitor the enteric virus concentration in the reclaimed water generated by two sewage treatment plants (STP) with different multibarrier technologies, and to assess if stringent treatment extent is required in a low-resource setting to achieve minimal viral risks arising from non-potable reuse. Through a 9-month surveillance, it was observed that a higher diversity and abundance of enteric DNA and RNA viruses were detected in treated wastewater generated from conventional activated sludge (i.e., site B) compared to that from membrane bioreactor-based STP (i.e., site A). To exemplify, enteric RNA viruses were detected in up to 1.13, 4.1, 4.9, 4.5, and 4.5 log10 copies/L for Aichi virus (AiV), rotavirus (RV), enterovirus (EV), norovirus GI and GII (NoV GII, GII) respectively, at site B. For enteric DNA virus, up to 4.3 and 5.35 log10 copies/L of adenovirus (AdV) and polyoma BK virus (BKV) were also found in site B. This is in contrast to the absence of AiV, RV and NoV detected in samples from site A. However, when translated to risks outcome from NoV GII, it was noted that recreational users at both sites A and B are exposed to acceptable disease burden (<10−4 DALYpppy). Occupational workers at site B faced burden risk of 2.01 × 10−4 to 3.85 × 10−4 DALYpppy, which is slightly higher than the acceptable 10−4 DALYpppy but such level of risks can be reduced by minimizing exposure frequency and/or adoption of best management practices. Findings from this study suggest that additional implementation of treatment barriers that incur higher capital investment or energy costs in low resource countries may not be mandatory to mitigate risks arising from enteric viruses for non-potable reuse purposes studied here. [Display omitted] •Higher diversity of viruses in treated wastewater from activated sludge (site B) than MBR (site A).•Enterovirus (EV) was present at higher concentration than adenovirus and polyoma virus (BKV) at site A.•Concentrations of BKV > EV > Norovirus GII and GI > Aichi virus > and rotavirus at site B.•Higher viral abundance at site B did not translate to significant risks for recreational users.•NoV GII QMRA showed 2.01 × 10−4 to 3.85 × 10−4 DALYpppy for workers at site B, site A remains <10−4 DALYpppy.